Keterampilan Guru Bahasa Indonesia Sma Negeri 1 Tengaran Dalam Menerapkan Pembelajaran Berpendekatan Saintifik - PURNAMA, ARYANI (2016)
THE SKILL OF THE INDONESIAN LANGUAGE TEACHERS IN SMA I TENGARAN TO APPLY THE SCIENTIFIC APPROACH LEARNING Aryani Purnama, S200140043, Magister of Scholary Research of Indonesian, Graduate of Muhammadiyah University Surakarta, 2015, xx+p.148 The research has four goals. First, to describe the skill of Indonesian language teachers in SMA N 1 Tengaran to design the planning of learning implementation with scientific approach. The second, to describe the skill of Indonesian language teachers in SMA N 1 Tengaran to do the scientific approach in the learning implementation. Third, to identify the obstades of the Indonesian language teachers in SMA N 1 Tengaran when doing the scientific approach in lesson. The fourth, to describe the solution of Indonesian language teachers in SMA N 1 Tengaran to solve their problems /obstades in scientific approach learning. This research is qualitative description. Source of the data research are the lesson activities and the planning of learning implementation document. The technical of information collecting are observation, interview and analysis the contents of Planning of Learning Implementation document. This observation has done by recording the activities lesson of the teacher and students. The results of this observation is confirmed with the results of the interview by teacher, students, and the headmaster of SMA N 1 Tengaran. The data of teachers skill can be seen in the analysis of Planning of Learning Implementation contents. From the result of the analysis can be conclused that the teacher skill to make Planning of Learning Implementation is not optimal yet. The skill of teachers in the scientific approach learning is various. The variety includes: (1) learning implementation with 5M steps (observing, asking, data collecting, associating, and communicating) and explanation, (2) the 5M in beginning with explanation, and (3) 5M learning is guided by debriefing. From the three variation can be concluded that the inductive reasoning concept and based on science as the main of scientific approach have not implemented yet in the lesson. The obstades of the teachers are the steps of asking, communicate, and the means learning based on informatics technology. The solutions are utilizing of text book as the main source of learning, variety methods, the technis of scientific steps and utilizing of environment as the learning source. Keyword: skill teacher, scientific approach